ANALISIS KARAKTERISTIK REDAMAN INFRASTRUKTUR TELEKOMUNIKASI TERPASANG (SERAT OPTIK) UNTUK MENDUKUNG KOMUNIKASI BROADBAND - Santoso, Triyono Budi (Industrial and Systems Engineering Assessment Journal (INASEA), 2014)
In the telecommunication industry, network infrastructure holds a major role to deliver excellent service and achieve higher Continuity of Service to the customer. The demand of capacity and broadband speed in good quality (Internet, video on demand, wireless broadband, etc) has brought a fundamental change in the infrastructure and must be prepared by provider in deploying fiber optic backbone as part of a reliable system with the lowest attenuation. Factorial Design and Analysis of Experiments were used to get exact results that attenuation is determined by related components such as fiber optic brand, type of splicer, type of fiber termination and the location placed. Power Budget analysis is needed in deploying all the communication system, besides Operation and Maintenance activities in managing and monitoring the quality in real time mode. So when there is a fault in the system, it could be warned and recovered immediately. This gives signs to all telecommunication industry parties (provider, vendor, and regulator) to give mutualism contribution in providing reliable services to the customer.